An isolated multi-port bidirectional DC-DC converter for EV applications. (2022) - Ramesh, P.; Kumar Gouda, Pramod; Rameshbabu, A.; Ramanathan, G.; Bharatiraja, C.
Highlights: A multi-port isolated dc–dc converter with the fewest possible switches has been proposed. The proposed multi-port dc–dc converter has the benefit of having a simple topology while being capable of MPPT management for many renewable energy sources concurrently. The converter was used to regulate the power output of a three-source battery/solar hybrid generating system concurrently. Abstract: The challenges in combination of multiple renewable energy sources (RES) in the direction of meet the load requirement is overcome by suitable design of multi-input topology. This paper recommends a three-input DC-DC converter topology with two photovoltaic cells, and one battery providing additional storage. The independent control of input sources enhances the converter reliability during the failure of any one input unit. In addition, the energy storage system is charged by the output port for continual operation. The combinations of switching states and respective four operating scenarios are discussed. The small signal model of the planned multi-port isolated bidirectional DC-DC converter derived and the stability for all possible scenarios are confirmed for open loop system as well the closed loop controller using K-factor method. The proposed converter is simulated with variable input sources using MATLAB / 2015A software. As compared with existing topologies, all ports are controlled and regulated by employing MPPT technique for input renewable energy ports, Constant Current Constant Voltage (CCCV) control scheme for battery port and modified PI regulator for load port. The model is validated by developing a hardware prototype of power rating 500 W, 72 V and its performance efficiency curves are plotted and verified.